2020
DOI: 10.3390/cancers12040774
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapies: Friends or Foes for Patient’s NK Cell-Mediated Tumor Immune-Surveillance?

Abstract: In the last 20 years there has been a huge increase in the number of novel drugs for cancer treatment. Most of them exploit their ability to target specific oncogenic mutations in the tumors (targeted therapies–TT), while others target the immune-checkpoint inhibitor molecules (ICI) or the epigenetic DNA modifications. Among them, TT are the longest established drugs exploited against a wide spectrum of both solid and hematological tumors, often with reasonable costs and good efficacy as compared to other inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 190 publications
(229 reference statements)
0
14
0
Order By: Relevance
“…These different responses could explain why the inhibition of the JAK/STAT pathway may have unexpected effects, such as those shown by Bottos et al, who found that the inhibition of JAKs with NVP-BSK805 and ruxolitinib (JAK1/2 inhibitor) in experimental models of breast cancer improved metastasis by inhibiting the maturation, activation, proliferation, and cytotoxicity of NK cells [ 170 ]. The inhibitor ruxolitinib reduces Treg cell levels and decreases dendritic cell differentiation, migration, and activation, in addition to increasing the rate of infections [ 171 , 172 , 173 ]. These findings stress the importance of analyzing the adverse effects of the inhibitors of the JAK/STAT pathway on cancer immunosurveillance.…”
Section: Inhibition Of the Jak/stat Pathway As A Therapeutic Targementioning
confidence: 99%
“…These different responses could explain why the inhibition of the JAK/STAT pathway may have unexpected effects, such as those shown by Bottos et al, who found that the inhibition of JAKs with NVP-BSK805 and ruxolitinib (JAK1/2 inhibitor) in experimental models of breast cancer improved metastasis by inhibiting the maturation, activation, proliferation, and cytotoxicity of NK cells [ 170 ]. The inhibitor ruxolitinib reduces Treg cell levels and decreases dendritic cell differentiation, migration, and activation, in addition to increasing the rate of infections [ 171 , 172 , 173 ]. These findings stress the importance of analyzing the adverse effects of the inhibitors of the JAK/STAT pathway on cancer immunosurveillance.…”
Section: Inhibition Of the Jak/stat Pathway As A Therapeutic Targementioning
confidence: 99%
“…The CD94/NKG2A heterodimer, specific for HLA-E, is expressed first during NK cell differentiation. Later, it may be co-expressed with KIR(s) which recognize allotypic determinants of HLA-A, while it is lost by the most mature NK cells which express KIR(s) only [ 16 , 17 ]. In a healthy environment, resting NK cells express HLA class I molecules that generate inhibitory signals via KIR or NKG2A, while, NK cell activation is dependent on an array of activating receptors and co-receptors, including natural cytotoxicity receptors (NCR, i.e., NKp46, NKp30, and NKp44), NKG2D, DNAM-1, and CD16, that interact with ligands overexpressed or expressed de novo on tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…ILCs are further divided into ILC1s, ILC2s, ILC3s, and lymphoid tissue-inducer (LTi) cells. 66 NK cells functionally mirror CD8 + T cells because they exhibit antitumor cytotoxic activity. In comparison, ILC subsets are tissue-resident populations with analogous roles to CD4 + T helper (Th) cell subsets.…”
Section: Introductionmentioning
confidence: 99%
“…Solid tumors, such as renal cell carcinoma, can be heavily infiltrated by NK cells. 66 These innate lymphocytes are regulated by constitutively expressed activating and inhibitory receptors, which recognize stress-induced ligands and various conserved motifs on class I and non-canonical MHC molecules. 68 There are conflicting reports as to whether NK cells express significant levels of PD-1.…”
Section: Introductionmentioning
confidence: 99%